2008
DOI: 10.1099/vir.0.2008/001792-0
|View full text |Cite
|
Sign up to set email alerts
|

Formation of bovine viral diarrhea virus E1–E2 heterodimers is essential for virus entry and depends on charged residues in the transmembrane domains

Abstract: The envelope of bovine viral diarrhea virus (BVDV) contains the glycoproteins E rns , E1 and E2. Complementation of a recombinant vesicular stomatitis virus (VSV) with BVDV glycoproteins resulted in infectious pseudotyped viruses. To elucidate the specific role of each of the single envelope glycoproteins during viral entry, pseudotypes were generated bearing the BVDV envelope proteins in different combinations. Pseudoviruses that contained E1 and E2 but not E rns were infectious, indicating that E rns is disp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
71
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(74 citation statements)
references
References 29 publications
(25 reference statements)
2
71
1
Order By: Relevance
“…A similar observation has been made with other viruses; a single substitution of conserved Cys171 to Ser (Fig. 1), located in the putative transmembrane domain of E1 protein, in the context of a BVDV E1-and E2-pseudotyped vesicular stomatitis virus, did not preclude formation of heterodimers or virus infectivity (13). It is possible that in these single-site mutants other interactions may contribute to formation of heterodimers and overall efficiency of the viral infection.…”
Section: Discussionmentioning
confidence: 52%
See 1 more Smart Citation
“…A similar observation has been made with other viruses; a single substitution of conserved Cys171 to Ser (Fig. 1), located in the putative transmembrane domain of E1 protein, in the context of a BVDV E1-and E2-pseudotyped vesicular stomatitis virus, did not preclude formation of heterodimers or virus infectivity (13). It is possible that in these single-site mutants other interactions may contribute to formation of heterodimers and overall efficiency of the viral infection.…”
Section: Discussionmentioning
confidence: 52%
“…It is possible that in these single-site mutants other interactions may contribute to formation of heterodimers and overall efficiency of the viral infection. Ronecker et al (13) observed that substitutions of conserved Lys174Ala and Arg177Ala in BVDV E1 (Fig. 1) significantly reduced the formation of heterodimers in cells infected with pseudotyped viruses, indicating that these charged amino acids in the transmembrane domains of BVDV E1 also contribute to the interaction with E2.…”
Section: Discussionmentioning
confidence: 99%
“…Viruses from the two genera have similar morphologies in electron micrographs and contain only two envelope glycoproteins, E1 and E2 (3)(4)(5). Moreover, formation of E1-E2 heterodimers through interactions involving the transmembrane segments of the two proteins is required for cell entry of both pesti-and hepaciviruses (22,23). In HCV, as in pestiviruses, E1 is half the size of E2, which is the immunodominant protein and binds a cellular receptor that is not efficiently internalized (8,9).…”
Section: Discussionmentioning
confidence: 99%
“…BVDV E2 forms disulfide-linked homodimers and heterodimers with E1 (19)(20)(21). Formation of BVDV E1-E2 heterodimers is essential for virus entry and depends on charged residues in the transmembrane segments of the two glycoproteins (22). Similarly, in HCV the transmembrane segment of E2 is required for correct folding and assembly of E1-E2 heterodimers (23).…”
mentioning
confidence: 99%
“…The envelope protein E rns , which lacks a typical membrane anchor, seems to be important for first cell contact by binding to glycosaminoglycans (Fetzer et al, 2005;Iqbal et al, 2000). The cellular receptor for BVDV is the bovine CD46 molecule and it has recently been shown that E1-E2 heterodimers are essential for virus entry (Maurer et al, 2004;Ronecker et al, 2008). The envelope proteins E rns , E1 and E2 are processed from the polyprotein in a hierarchical way, starting with the translocation of the C-terminal signal peptide downstream of the capsid protein into the endoplasmic reticulum (ER), followed by the release of the capsid and E2 protein (Heimann et al, 2006; Rümenapf et al., 1993).…”
mentioning
confidence: 99%